2018
DOI: 10.1038/s41598-018-33231-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cationized gelatin nanospheres incorporating molecular beacon to visualize cell apoptosis

Abstract: The objective of this study is to prepare cationized gelatin nanospheres (cGNS) incorporating a molecular beacon (MB), and visualize cellular apoptosis. Two types of MB to detect the messenger RNA (mRNA) of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (GAP MB), and caspase-3 (casp3 MB) were incorporated in cGNS, respectively. MB incorporated in cGNS showed the DNA sequence specificity in hybridization. The cGNS incorporation enabled MB to enhance the stability against nuclease to a significantly great exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…This can be due to the limited access of DNase I to the MB incorporated in the complexes as well as the inhibited recognition of MB as a substrate of the nuclease. In addition, it has been demonstrated that incorporation in the cationized gelatin nanospheres could prevent MB from the degradation by DNase I [ 30 ]. Therefore, in the case of complexes prepared in this study, the anti-nuclease stability would be enhanced compared with the free MB although further study is required to comprehensively investigate the incorporation ability of MB and the consequent stability for various complexes prepared with different cationized gelatins and mixing ratios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be due to the limited access of DNase I to the MB incorporated in the complexes as well as the inhibited recognition of MB as a substrate of the nuclease. In addition, it has been demonstrated that incorporation in the cationized gelatin nanospheres could prevent MB from the degradation by DNase I [ 30 ]. Therefore, in the case of complexes prepared in this study, the anti-nuclease stability would be enhanced compared with the free MB although further study is required to comprehensively investigate the incorporation ability of MB and the consequent stability for various complexes prepared with different cationized gelatins and mixing ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The complexation of cationized gelatin and MB was performed by simply mixing cationized gelatin solution and MB in DDW [ 30 ] at different mixing ratios (5, 10, 20, 40, and 200 pmole MB/μg cationized gelatin). The mixed solution was incubated for 15 min at room temperature to obtain the cationized gelatin-MB complexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then the solutions were mixed with an appropriate amount of 1× binding buffer, and placed on ice. The samples were evaluated using flow cytometry within 1 h (Liang et al, 2017;Murata et al, 2018;Sui et al, 2018b;Zhao et al, 2018).…”
Section: Flow Cytometrymentioning
confidence: 99%